Pengembangan Ensiklopedia Digital Kearifan Lokal Kabupaten Kediri Untuk Meningkatkan Literasi Budaya Pada Siswa Sekolah Dasar - Nur Husna Afandi, Alia; Adhi Suciptaningsih, Oktaviani; Pristiani, Riska; Slamet (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This research is based on the problem of learning resources that are not yet included in the independent curriculum and teachers' difficulties in finding relevant learning resources. The aim of this research is to produce teaching materials in the form of a digital encyclopedia of Kediri district local wisdom containing folklore, traditions, arts, typical clothing, tourism and typical food to develop valid, practical and effective fourth grade elementary school students' cultural literacy. This digital encyclopedia was developed in a structured manner involving analysis, planning, production and evaluation stages, guided by the Richey & Klein (2009) development model. The construction validation process resulted in a score of 90%, while material suitability validation was 89%. Both score results can be categorized as